Utilization of Educational Radio as a Learning Media in SMP Negeri 4 Padang Panjang - Yusman, Ahmad Fauzan; Sarah, Ririn Amaliah Putri; Ardipal, Ardipal; Efi, Agusti; Gistituati, Nurhizrah (Jurnal Basicedu, 2021)
This article discusses the use of educational radio owned by SMP Negeri 4 Padang Panjang. This article uses a qualitative research method with a descriptive analysis approach. The participation of the use of information technology in learning media is considered strategic, especially in learning during the Covid-19 pandemic. Government policies that limit community activities, including restrictions on face-to-face learning in schools, have initiated various parties to develop learning media that can be used remotely. The various media developed are very diverse, ranging from print-based media such as modules or student activity sheets to technology-based media such as learning videos or learning broadcasts. Radio Education 104.5 FM, which was initiated by SMP Negeri 4 Padang Panjang, is the right choice to maintain interactive learning for students at SMP Negeri 4 Padang Panjang and Padang Panjang City students in general.